Da crise à oportunidade: o papel contingente da folga organizacional - Silva, Adriano Cavalcante da (2019)
In this research, financial slack is considered as a resource under the management's criterion, which can assume a contingent role to respond to discontinuities in the environment, create innovation and change and, trus, improve a company's response to environmental changes. During the growth process of companies, the emergence of slack is natural, and necessary, leading economic agents to decide in what type of assets these idle resources will be allocated, bearing in mind that, once allocated, they will have different liquidity and profitability attributes. This decision becomes even more important, when the economic environment where the companies are located, presents great instability. Thus, the objective of this research was to measure the probability of each type of organizational slack, to contribute to the better performance of companies, when they face periods in crisis and growth. With accounting data from 281 publicly traded Brazilian companies, from the first quarter of 2007 to the first quarter of 2019 (n = 13,769 observations), the results of the binary response regression models for panel data indicated that in times of crisis, the chances obtaining better performance are reduced, on average, 0.09 times. However, the moderating effect of the crisis on the relationship between slack and performance was not statistically significant, leading to the non-acceptance of the first research hypothesis. Companies with greater investment opportunities, contrary to what was expected, had their chances reduced by up to 85.43%, but, when they have higher levels of available slack and recoverable slack, the chances of obtaining a performance above the expected, can increase up to 115 and 47.15 times respectively. The results suggest that the available slack is the best type of organizational slack to be maintained by the companies, while the recoverable and potential slack should be avoided, unless they have great investment opportunities, in this case, a certain level of recoverable slack can also be maintained.